Review: Leptin gene expression in the placenta - Regulation of a key hormone in trophoblast proliferation and survival - Maymo, Julieta Lorena (2011)
Leptin is a 16000 MW protein originally described as an adipocyte-derived signaling molecule for the central control of metabolism. However, pleiotropic effects of leptin have been identified in reproduction and pregnancy. The leptin gene is expressed in placenta, where leptin promotes proliferation and survival of trophoblast cells. Study of the major signaling pathways known to be triggered by leptin receptor has revealed that leptin stimulates JAK/STAT, MAPK and PI3K pathways in placental cells. Leptin also exerts an antiapoptotic action in placenta and this effect is mediated by the MAPK pathway. Moreover, leptin stimulates protein synthesis by activating the translational machinery via both PI3K and MAPK pathways. Expression of leptin in placenta is highly regulated, suggesting that certain key pregnancy molecules participate in such regulation. An important hormone in reproduction, hCG, induces leptin expression in trophoblast cells and this effect involves the MAPK signal transduction pathway. Moreover, the cyclic nucleotide cAMP, which has profound actions upon human trophoblast function, also stimulates leptin expression and this effect seems to be mediated by crosstalk between the PKA and MAPK signaling pathways. Estrogens play a central role in reproduction. 17b-estradiol upregulates leptin expression in placental cells through genomic and non-genomic actions, probably via crosstalk between estrogen receptor-a and the MAPK and PI3K signal transduction pathways. Taken together these findings give a better understanding of the function of leptin and the regulatory mechanisms of leptin expression in human placental trophoblast and further support the importance of leptin in the biology of reproduction.